Emerging Environmental Technologies, Volume II - Shah, Vishal; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
While numerous journals and books are available in the market highlighting the developments in the field of environmental technology, none of them exclusively focuses on the technologies that would be in the forefront in near to far future. Each and every article in the book is peer-reviewed and from a different sub-discipline. Because of its interdisciplinary topics on for instance air pollution and energy production, this makes it a one book for all and serves as an excellent resource for scientists, entrepreneurs, politicians and non-governmental organizations who wish to gain information on upcoming and promising technologies.
Immobilization of Uranium in Groundwater Using Biofilms -- Encapsulation of Potassium Permanganate Oxidant in Biodegradable Polymers to Develop a Novel Form of Controlled-Release Remediation -- Decontaminating Heavy Metals from Water Using Photosynthetic Microbes -- Noise: The Invisible Pollutant that Cannot Be Ignored -- Energy Production from Food Industry Wastewaters Using Bioelectrochemical Cells -- Needle-Type Multi-Analyte MEMS Sensor Arrays for In Situ Measurements in Biofilms -- Fundamentals and Applications of Entrapped Cell Bioaugmentation for Contaminant Removal -- Biofuels for Transport: Prospects and Challenges -- Floating Vegetated Mats for Improving Surface Water Quality.
Keywords: Environmental sciences; Waste disposal; Sustainable development; Environment; Environment, general; Waste Management/Waste Technology; Sustainable Development